The PTPN22 R263Q polymorphism is a risk factor for rheumatoid arthritis in caucasian case-control samples. - Rodríguez-Rodríguez, L; Wan Taib, W; Topless, R; Steer, S; González-Escribano, M; Balsa, A; Pascual-Salcedo, D; González-Gay, M; Raya, E; Fernandez-Gutierrez, B; González-Álvaro, I; Bottini, N; et al. (2010)
OBJECTIVE: Recently a functional PTPN22 variant (R263Q rs33996649) was associated with systemic lupus erythematosus (SLE). The aim of this paper was to analyze the influence of this polymorphism on the risk of RA METHODS: 5,579 RA patients were recruited from outpatient clinics from 6 different countries: Spain, New Zealand, UK, Norway, The Netherlands and Germany. 5,392 healthy controls (HC) were recruited from the same areas. There was 100% power to detect an effect equivalent to that observed in SLE. Samples were genotyped for PTPN22 R263Q rs33996649 and PTPN22 R620W rs2476601 polymorphisms using a TaqMan 5´ allele discrimination assay. The effect of the R263Q variant was analyzed in isolation and conditional on the effect of R620W using UNPHASED and STATA 10 software. RESULTS: Minor allele A of PTPN22 R263Q was significantly associated to a lower RA risk in the pooled analysis of the 6 populations (M-H pooled OR 0.80 [0.67-0.96], p=0.016), independent of the effect of the R620W polymorphism. Both polymorphisms had an additive effect: the more RA risk alleles carried (R263Q G allele, R620W T allele), the higher the RA risk (2 vs.1 p=0.014, OR 1.28 [1.05-1.55], 3 vs. 1 p=6.67×10(-11), OR 2.01 [1.63-2.48] and 4 vs. 1 p=6.50×10(-11), OR 3.55 [2.42-5.20]). CONCLUSIONS: The minor allele of the PTPN22 R263Q polymorphism is associated to a lower RA risk. This association is independent of the well-established association between PTPN22R620W and RA. Both polymorphisms exerted an additive effect on the risk of RA.